Aspectos de producción, comercialización y desarrollo del cultivo de pitahaya (Hylocereus spp.) en el litoral ecuatoriano - García Solís, Joel Alexander (2021)
The pitahaya (Hylocereus spp) is a Cactaceae species that presents great nutritional and commercial potential and currently occupies an important space in the agricultural sector. The pitahaya has gained recognition as an exotic fruit, being demanded in markets such as the United States, and several countries in Europe and Asia. In the country, pitahaya (yellow and red) is produced between 12,000 and 15,000 kilos ha-1, the international market being the destination of a large percentage of local production. Thus, this item has great potential for agricultural development, being an alternative for the implementation of an agribusiness for small and medium producers. Given the above, the objective of this bibliographic work was to collect information related to the production, commercialization and development of the pitahaya cultivation in the Ecuadorian coast. The production of pitahaya requires a process with high added value. For producing countries, it is convenient to export high volumes of fruit to supply internal and external demand. This process involves the use of agricultural inputs, investment, logistics process and a greater number of personnel involved in the fruit agribusiness chain. To achieve further expansion of the pitahaya production areas, especially on the Ecuadorian coast, it is necessary to establish an administrative structure for export. Given this, cooperation between government, private or NGO entities and the pitahaya producing sector is necessary to define lines of research focused on genetic improvement, efficient crop management and commercialization, thus allowing the continuous supply of the national and international market. .